Problems and Solution Suggestions Related to Logistics Processes in Cross-Border E-Commerce: Evaluations Towards E-Export in Bursa Province - Sonmezay, Mine; Keser, Hilal Yıldırır (My University, 2024)
Rapidly growing e-commerce, due to globalization and the impact of the Covid-19 epidemic, has significantly increased global demand, and cross-border e-commerce has become a frequently mentioned concept. Cross-border e-commerce, which also triggers the development of international trade, has begun to influence the economic policies of countries, especially with its e-export dimension. The most important factor behind the development and success of cross-border e-commerce can be expressed as being its logistics services. E-commerce processes achieve success with the effectiveness of these services. However, as in many countries, problems may occur in logistics processes in Türkiye, which may prevent cross-border e-commerce companies from using their potential. In this context, in the study, firstly, the concepts of e-commerce and cross-border e-commerce are discussed and the concept of e-export is clarified. Then, logistics services in cross-border e-commerce are explained. Finally, a qualitative research is conducted to reveal the logistics problems encountered in cross-border e-commerce, and the findings of in-depth interviews with companies engaged in e-export in Bursa are evaluated.
Keywords: E-Commerce; E-Export; Cross-Border E-Commerce; E-Commerce Logistics